(untitled) (Bangladesh Heart Journal, 2021)
Background: Noninvasive assessment of arterial stiffness with aortic pulse wave velocity (PWV) may serve as a useful adjunct to the cardiovascular risk stratification and risk management. The aim of this study was to evaluate the association between aortic PWV and severity of coronary artery disease (CAD) in patients with non-STsegment elevation myocardial infarction (NSTEMI). Methods: This cross sectional analytical study was conducted over 100 NSTEMI patients who were purposively selected and agreed to do coronary angiogram during index hospital admission. PWV was assessed noninvasively using the SphygmoCor® system on the day before coronary angiogram (CAG). Study subjects were divided into two groups on the basis of PWV. In group I: PWV was ≤10 m/sec and in group II: PWV was > 10 m/sec. Fifty patients in each group. Angiographic severity of CAD was assessed by vessel score, Friesinger score and Leaman score. Results: Vessel score 2 and 3 were significantly (p<0.05) higher in group II and vessel score 0 and 1 were significantly (p<0.05) higher in group I. The mean PWV in the group with normal angiographic results was 8.21±1.8 m/sec, and in patients with single-vessel disease it was 9.88±2.02 m/sec. In those with double and triple vessel disease the mean PWV was found 11.95±2.61 m/sec and 14.37±2.96 m/sec respectively. There was a significant difference of the mean value of PWV among the vessel involvement group (p=0.001). Normal and low Friesinger score were significantly (p<0.05) higher in group I patients. Intermediate and high Friesinger score were significantly (p<0.05) higher in group II patients. Increased PWV was significantly associated with the presence and severity of CAD in NSTEMI. This association showed a positive linear relation between the values of PWV and vessel score (r=0.65, p=0.01), Friesinger score (r=0.61, p=0.01), and Leaman score (r=0.36, p=0.01). Conclusion: From this study it may be stated that arterial stiffness, as measured by the aortic PWV, is an independent predictor of the presence and extent of CAD. Measurements of aortic PWV in NSTEMI can detect high risk patients requiring an early invasive strategy over a delayed invasive strategy. Bangladesh Heart Journal 2021; 36(1) : 38-46